ANTIBACTERIAL ACTIVITY Streptomyces spp. ENDHOPHYTIC TO Staphylococcus aureus AND Eschericia coli - Siti Nur Azizah (AKADEMI FARMASI JEMBER, 2021)
The objective of this research was to known antibacterial activity of 4 endhophytic Streptomyces namely Streptomyces griseorubiginosus, Streptomyces vellosus, Streptomyces diastaticus and Streptomyces griseoruber against Staphylococcus aureus and Eschericia coli and measure the biggest antibacterial activity which is indicate by clear zone diameter. Antibacterial activity by using agar plug diffusion method showed that Streptomyces vellosus has capable to inhibits growth of Staphylococcus aureus but not with Eschericia coli and Streptomyces diastaticus has capable to inhibits growth of Eschericia coli but not with Staphylococcus aureus. The clear zone of Streptomyces vellosus and Streptomyces diastaticus are 5,18 mm and 7 mm respectively. Streptomyces griseoruber and Streptomyces griseorubiginosus can’t grow during isolation. Keyword: Streptomyces vellosus, Streptomyces diastaticus, agar plug diffusion method